If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(1) + 8 = 2 Multiply -2 * 1 -2 + 8 = 2 Combine like terms: -2 + 8 = 6 6 = 2 Solving 6 = 2 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 4t^2-40+25=0 | | 0.2x=2.6x-2.8 | | Y=1/3(90-X)-6 | | Y=24-X/3 | | 10-4(3x+1)-(3x-4)= | | 6y-2x=1x | | 5-8x-2x=25 | | 2/7×-7 | | 1(1)-3(-2)+(-2)(-2)= | | 2/3(n-5/6)=5/2 | | 7/10=1/5x | | a1/3 | | 7/9(x-3/7)=7/3 | | 7/9*2 | | x+(x+18)= | | -3(2-9)-4(6-1)= | | 10x-2(x-8)=14whatisx | | 4(5*7)=5(4*7) | | 9(x-3)=8(3+x) | | -3x+1+9x=2(3x-2) | | -13+5x=-73 | | 5x+2(3x+8)+4= | | -7(x-3)-(-3x-9)=-5x | | x/11/x^2/22 | | X=1/3(90-X)-6 | | 6a+4+a+4a= | | 3(x+2)=2x-2 | | (2x-7)(3x+1)=(2x-5)(3x+2) | | 2x+3(x-1)=11+5x-14 | | -3+-1=-2 | | 2(1+5t)+6= | | -2+0=-2 |